الدراسات البلاغية وعلاقتها بعلم الدلالة: دراسة في مفهوم المجاز / Rhetorical studies and their relation with semantics: A study in the concept of figurative speech - عبد الله, نسيمة الحاج (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2016)
ملخص البحث: حظيت الدراسات البلاغية بعناية كبيرة من قبل العلماء الأوائل بدءاً من القرن الثاني الهجري حتى وصلتْ مرحلةَ النضج في القرن الثامن الهجري. وقد انبثق مصطلح )علم الدلالة( من علم اللغة الحديث في أواخر القرن التاسع عشر الميلادي، ويقابل علم الدلالة في العربية المصطلحَ الإنجليزي ) Semantics (. لا يخفى أن المجاز له شأنٌ كبيرٌ في الدراسات البلاغية العربية، قبل أن يصبح جانباً من الجوانب التي تتناولها دراسات علم الدلالة في باب التغرير الدلالي ) Semantic Change (. من أجل ذلك حاولتْ الباحثة توضيح أن ثمة نطاقاً متداخلاً متشابك اً بين علم الدلالة والدراسات البلاغية خاصة فيما يترصل بالمجازات بغية الوصول في نهاية المطاف إلى معرفة وجهات التناول المتشابهة والمتباينة بين ذانك المجالين. تو ر صلت الباحثة إلى أن علم الدلالة علم عام يتناول اللغات جميعاً وليس لغة بعينها، أما الدراسات البلاغية فتعالج الخصائص الخاصة بعلوم البلاغة العربية؛ فالدراسات البلاغية أخص، وعلم الدلالة أعم منها. وعلى الرغم من ذلك كله، يتناول علم الدلالة جزءاً من الفنون البلاغية بوصفها جزءاً من دراسته، والقوانين التي يكتشفها علم الدلالة ستكون قابلة للتطبيق على تلك الفنون البلاغية. الكلمات المفتاحية: البلاغة الدراسات علم الدلالة الانتقال الدلالي المجاز. - - - - Abstract: Rhetorical studies had been given significant attention by the traditional scholars from the second century of Hijrah until the eighth century Hijrah when they reached the period of maturity. Semantic on the other hand is a term that emerged in the realm of modern linguistics at the end of the nineteenth century C.E. Figure of speech was an important topic in rhetoric before it also became a topic in semantics in the case of semantic change. The writer in this paper will try to argue that there is an overlapping area between semantic and rhetoric specifically in relation to figure of speech. There are also differences in treating the subject in the two disciplines. The writer concluded that semantic is a field that deals generally with human language without specifically referring to a certain language but rhetoric was a discipline that was dedicated to studying Arabic rhetorical characteristics. On the other hand semantic also deals with certain aspect of rhetoric and what was observed semantically is applicable in the domain of rhetorical study as well. Keywords: Rhetoric – Studies – Semantic - Semantic transfer - Figure of speech. Abstrak: Kajian Ilmu Balaghah telah mendapat perhatian yang besar dalam kalangan ilmuwan Bahasa Arab semenjak daripada kurun ke dua Hijrah sehinggalah ke puncaknya pada kurun Hijrah yang ke lapan apabila ia menecah puncak kematangannya. Sematik pula adalah satu istilah untuk cabang ilmu yang timbul pada akhir kurun ke Sembilan masehi. Ungkapan kiasan adalah satu topik penting dalam ilmu balahghah Arab sebelum ia turut dikaji dalam disiplin semantik berkenaan dengan perubahan makna. Penulis dalam kajian ini mencadangkan bahawa terdapat persamaan lapangan di antara semantic dan ilmu balaghah terutama dalam tajuk ungkapan kiasan. Namun terdapat juga perbezaan perspektif dan pendekatan dalam mengkaji tajuk tersebut dalam kedua-dua disiplin itu. Penulis juga merumuskan bahawa semantik ialah satu bidang yang mengkaji secara umum tentang bahasa manusia tanpa merujuk kepada sifat khusus sesuatu bahasa manakala ilmu balaghah pula ialah satu cabang kajian yang khusus berkenaan dengan aspek retorik Bahasa Arab. Pada masa yang sama semantik juga turut mengkaji beberapa aspek retorik bahasa dari aspek semantik dan ini turut mendapat perhatian dalam kajian retorik Ilmu Balaghah. Katakunci: Retorik – Kajian – Sematik - Perpindahan makna - Ungkapan kiasan.